Total ankle replacement in young patients - Samaila, Elena Manuela; Bissoli, Andrea; Argentini, Emanuele; Negri, Stefano; Colò, Gabriele; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
High physical demand and younger age are currently considered contraindications for total ankle replacement. The number of Total Ankle Replacements (TAR) is widespread increasing and indications are expanding thanks to a steady improvement in prosthetic designs and better outcome. Commentary of the literature: in 1999 a study of 100 uncemented STAR™ (Waldemar-Link, Hamburg, Germany) prostheses showed a survival rate of 75% at 6.8 years in patients under 50 years old. Other studies (es, Barg et Al.) shows the risk of failure age-related in young patients compared to older group. A report of 780 TAR from the Swedish Ankle Register showed patients with primary or post-traumatic osteoarthritis under 60 years of age to have a 1.8 higher chance of revision compared to older patients. Discussion: ankle replacement has been traditionally reserved for patients older 50 years old and with low physical demand. Contrariwise this belief, TAR have already been used with a wide range of ages, sometimes even patients younger than 30 years old. Most of the “negative” score and results showed before are related to “second-generation” prosthetic designs, while recent studies used a “third-generation” prosthetic design. Conclusions: recent evidences showed better clinical results and higher satisfaction in people under the age of 50 compared to ankle arthrodesis with comparable rate of complications and survivorship. Younger people will have however a higher rate of reoperation but in the meantime, they will prevent progressive degeneration of adjacent joints.